Addressing the Soil Infertility Conundrum through Agroforestry: Empirical Evidence from Cameroon - Tsufac, Azembouh Roshinus; Awazi, Nyong Princely; Tchamba, Martin Ngankam (Challenging Issues on Environment and Earth Science Vol. 7, 2021)
Agricultural productivity depends largely on the fertility of the soil. However, in recent years, soil infertility has been the trend across the world driven mainly by climate change and poor agricultural practices. In sub-Saharan Africa in general and Cameroon in particular, soil infertility is a major stumbling block to the growth of the agricultural sector. It was within this backdrop that this study was carried out to ascertain the role that agroforestry can play towards enhancing soil fertility in agricultural systems in south western Cameroon. Both biophysical and socio-economic data were collected and analyzed using Excel 2013 and SPSS 17.0 through descriptive and inferential statistics. Findings showed that the main constraints to crop productivity were inaccessibility to improved planting materials (100%) and little or no control of stress factors like soil infertility (100%). Farmers made use of different types of agrochemicals with the most common being insecticides and fungicides. Three main agroforestry systems namely agrosilvicultural (93%), agrosilvopastoral (70%) and silvopastoral (31%) systems were practiced by farmers. The most common indicators of soil infertility identified by farmers were decline in crop yields (100%), rotting of tubers (100%) and wilting of crop stems (100%). The most common practices used to counter soil infertility were agro-chemicals, fowl droppings, improved planting seeds, erosion controlled farming, horizontal bunds or ridges on steep terrain, and agroforestry. The main impacts of soil infertility on farmers were difficulties in feeding, difficulties attending to social needs of children and the family, and financial difficulties. Farmers’ vulnerability to the adverse effects of soil infertility were exacerbated by high prices of inputs, low prices of farm produce, poor seeds/planting materials and bad roads. Live fences and scattered trees on croplands were the two most common agroforestry practices of farmers confronted with soil infertility. Analysis of different soil parameters (N, P, K and others) showed that scattered trees on croplands contributed more towards improving soil fertility which could be attributed to the diverse nature of the tree species found in the system and the dispersed nature of the trees on the entire farmland. Based on these findings, we recommend that more farmers adopt the practice of scattered trees on croplands in order to improve the fertility of their farmlands. Policy makers should also put in place favourable policies which encourage the practice of agroforestry.